Everyday cognition: historical and methodological approach - Dozhdikova, Raisa N. (Journal of the Belarusian State University. Philosophy and Psychology, 2021)
The logic of scientific research of everyday cognition demands the analysis of the theoretical premises of modern understanding of this phenomenon. The historical and logical methods of scientific cognition were used in the process of this analysis. The author has attempted to systematise philosophical approaches to the understanding of everyday cognition. The author comes to the conclusion that the analysis of the theoretical sources of modern understanding of everyday cognition allows to identify its specific feathers and prospects for further research.